Pengaruh Pemahaman, Kesadaran, dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi Karyawan di PT Energi Graha Sagara Batam - Najma Aulia Rizky; Khadijah Khadijah; Ferdila Ferdila; Andi Hidayatul Fadlilah; Baru Harahap (Economic Reviews Journal, 2026)
This study aims to analyze the effect of understanding, awareness, and tax sanctions on employee individual taxpayer compliance at PT Energi Graha Sagara Batam. The background of this study is based on the importance of taxpayer compliance in supporting state revenue and the existence of non- compliance phenomena in fulfilling tax obligations. This research employed a quantitative approach using a questionnaire distributed via Google Form to 100 respondents selected through total sampling technique. The data were analyzed using multiple linear regression with the assistance of SPSS version 25. The results show that partially understanding, awareness, and tax sanctions have a positive and significant effect on individual taxpayer compliance with significance values of 0.015 (<0.05), 0.000 (<0.05), and 0.000 (<0.05), respectively. Simultaneously, the three variables also have a significant effect on taxpayer compliance with an F-test significance value of 0.000 (<0.05). The Adjusted R² value of 0.220 indicates that understanding, awareness, and tax sanctions explain 22% of the variation in taxpayer compliance, while the remaining 78% is influenced by other factors outside this study. The findings imply that improving taxpayer compliance can be achieved through continuous tax education, increasing awareness of the importance of tax contributions to national development, and consistent enforcement of tax sanctions. This study is expected to serve as a reference for companies and related institutions in formulating policies to enhance taxpayer compliance in the workplace environment.